FEM and experimental analysis of thin-walled composite elements under compression - Różyło, Patryk; Wysmulski, Paweł; Falkowicz, Katarzyna (Zielona Góra: Uniwersytet Zielonogórski)
Thin-walled steel elements in the form of openwork columns with variable geometrical parameters of holes were studied. The samples of thin-walled composite columns were modelled numerically. They were subjected to axial compression to examine their behavior in the critical and post-critical state. The numerical models were articulately supported on the upper and lower edges of the cross-section of the profiles.
Keywords: thin-walled structures; Finite Element Method (FEM); numerical investigations; experimental investigations; buckling